Effects of dietary vitamins supplementation level on the production performance and intestinal microbiota of aged laying hens - Liping Gan; Yizhu Zhao; Tahir Mahmood; Yuming Guo (Poultry Science, 2020)
The objective of this study was to investigate the effects of higher vitamins supplementation level on the performance, immunity, and intestinal microbiota of old laying hens. Twelve birds were randomly chosen from 312 healthy, 65-wk-old Hy-Line Brown layers for sampling after a 7-wk acclimation period. The remaining 300 hens were randomly allocated to 1 of 4 dietary treatments for a 13-wk feeding trial: basal diet (CON), basal diet with 2-fold supplementation level of lipid-soluble vitamins (LV), 2-fold supplementation level of water-soluble vitamins (WV), or 2-fold supplementation level of both lipid-soluble and water-soluble vitamins (BV), respectively. Compared with 72-wk-old laying hens, the 85-wk-old laying hens showed declined egg quality, which implied by inferior eggshell strength and yolk color (P < 0.05). However, after 13 wks feeding trial, the birds in WV group had higher yellowness of yolk color, and LV group had increased laying rate (P < 0.05) compared with CON. Meanwhile, WV and/or BV groups showed improved GSH/GSSG levels in liver and increased secretory immunoglobulin A concentrations in jejunum compared with CON (P < 0.05). In addition, higher dietary vitamin supplementation levels significantly altered the composition of intestinal microbiota, as evidenced by increased abundance of ileal Lactobacillus, whereas reduced richness of ileal Romboutsia, Turicibacter, and cecal Faecalibacterium (P < 0.05) in WV group and increased cecal Megasphaera and Phascolarctobacterium (P < 0.05) in LV group compared with CON group. In conclusion, higher vitamin supplementation levels in the diet could improve laying performance and egg quality of aged hens, which was closely correlated with the increased abundance of beneficial microbiota in the intestine.